Ulama Perempuan di Panggung Pendidikan: Menelursuri Kiprah Nyai Hj. Nok Yam Suyami Temanggung - Indriati, Anisah (Jurnal Pendidikan Islam, 2014)
The term scholars, often associated with men. Though not denying the existence of women religious figures in Islamic history. Therefore, efforts to uncover side-scholars of women’s studies should be developed. This article discusses the thinking Ny. Hj. Nok Suyami and their work in the community. This qualitative research study life story that includes the source data obtained through interviews with domain analysis in Temanggung. This study concludes that the figure Hj. Nok Suyami qualify to be called as scholars’ because of some fundamental things inherent in him. Namely: (1) a qualified religious science capacity, (2) academic progression, (3) high human social life, (4) the ability to adapt to a good society, and (5) personal that is recognized by the society.